Culturas juvenis numa escola pública de ensino médio: novos usos, novos cenários - Barcelos, Karla Vello Meyrelles (2008)
Juvenile culture is a concept that is part of a theoretical repertory of some anthropologists whose works have renewed the study about youth (Pampols, 1999; Martin-Barbero, 1999; Reguillo, 1999; Margullis & Urresti, 1999; Islas, 1999; Valenzuela, 1999). The research, which was accomplished during 2005 and 2007, deals with juvenile cultures and with a public high school located in Vila Pompeia, west area of the city of Sao Paulo. The aim of this research is to understand the uses that young students have been producing of a public state high school that was investigated in the context of relations and social interactions that reveal, inside the school, different juvenile manifestations. Investigating the uses (De Certeau, 1994) that young students produce of the public school where they study shows, in a certain way, an interest in what they have been able to create, fabricate from the way the school offers itself to their consumption e by the relations which are established with the actors that compose the scholar universe. As hypothesis, it is believed that the juvenile cultures that are spread give opportunity to new uses of the public high school. It means that juvenile manifestations inside the school cannot be explained in a brief way, just viewed as indiscipline, pathology or bad behavior expressions of the youth. From Woods (1987; 1991) and Geertz (1989) ethnographic perspectives, the symbolic and concrete games that compose the juvenile manifestations in their sociability rites were considered. The methodological procedures we used were field observations, records, conversations, interviews, questionnaires and dossiers accomplishment. Young students from the first, the second and the third year from different shifts, teachers, inspectors, counterwoman, cleaning agent, and director were interviewed. The results point out that juvenile cultures are important and constituent parts of social functions assumed by the school. It was possible to prove that the school organization, with principles, rules, and values which are historically built is able to express the interactions and relations established by the young students inside the school. We can say that it is from concrete conditions and symbolic operations which are built together that we have the juvenile cultures and the new uses of the investigated public school